QUALITY ATTRIBUTE AND GEOGRAPHICAL INDICATION OF AGONLIN OIL (AGONLINMI) MADE IN BENIN - VIDEGLA, Euloge; GARBA, Kamal; FLOQUET, B. ANNE; TOSSOU, Hermann; MONGBO, ROCH LAMBERT; TOUKOUROU, FATIOU (My University, 2015)
The consumption frequency, the consumer’s income, the specific quality attribute and the consent to pay Agonlin oil, an oil of high standard made with a traditional knowledge is transferred from generation to generation in Agonlin region. According to its attributes, this oil has been evaluated through 400 consumers from 5 different districts or municipalities. The data collected have been analyzed thanks to a descriptive analysis. All in all, 10 attributes have been identified: the flavor, color, consistency, taste, local and natural character, nutritional value, geographical origin, viscosity and texture. The descriptive analysis shows its taste (60%) as being the main attribute of Agonlin oil, followed by its flavor (51%). The majority of interviewers consume Agonlin oil many times in a week (59%). But the oil is consumed by people with low income (40000 to 75000 FCFA). Other consumers with average income agree to value Agonlin oil when it is well manufactured and conserved. This study shows that Agonlin oil is a traditional and original product that the consumers agree to value. Consequently, Agonlin oil rightly deserves a geographical indication protection.
Keywords: Quality attributes; geographical attribute; specific quality; consent to pay.